STRATEGI PENGAMBILAN KEPUTUSAN BERBASIS RATIONAL OPTIMIZING DAN SATISFICING UNTUK TRANSFORMASI PENDIDIKAN EFEKTIF DI SMAN 15 PADANG - Sumiarni Sumiarni; Sufyarma Marsidin; Irsyad Irsyad (STKIP Pesisir Selatan, 2025)
This study examines the implementation of rational optimizing and satisficing-based decision-making strategies in educational transformation at SMAN 15 Padang. The principal, as an educational leader, is faced with complex decisions that require a strategic approach to achieve organizational effectiveness. This descriptive qualitative study used data collection techniques through in-depth interviews, observations, and documentation studies with informants such as the principal, vice principal, and teachers. The results show that SMAN 15 Padang applies a hybrid approach to decision-making by using rational optimizing for long-term strategic decisions such as the development of an independent curriculum and satisficing for daily operational decisions that require a quick response. The implementation of these two approaches has proven effective in improving learning quality, resource management efficiency, and stakeholder participation. This study recommends developing leadership capacity in decision-making skills through continuous training and the development of an educational management information system to support data-driven decision-making